2020
DOI: 10.3390/biom10020253
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Lon Protease: Novel Functions off the Beaten Track?

Abstract: To maintain organellar function, mitochondria contain an elaborate endogenous protein quality control system. As one of the two soluble energy-dependent proteolytic enzymes in the matrix compartment, the protease Lon is a major component of this system, responsible for the degradation of misfolded proteins, in particular under oxidative stress conditions. Lon defects have been shown to negatively affect energy production by oxidative phosphorylation but also mitochondrial gene expression. In this review, recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 91 publications
0
25
0
Order By: Relevance
“…5 ). A decreased level (fold change = 0.67; q = 4.20E-04) of mitochondrial Lon protease (LONP1), the major component of the mitochondrial protein quality control system under oxidative stress conditions [ 45 ], could have caused accumulation of misfolded proteins thus explaining this appearance. ER stress was enhanced in KO cells as revealed by dilated ER cisternae ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 ). A decreased level (fold change = 0.67; q = 4.20E-04) of mitochondrial Lon protease (LONP1), the major component of the mitochondrial protein quality control system under oxidative stress conditions [ 45 ], could have caused accumulation of misfolded proteins thus explaining this appearance. ER stress was enhanced in KO cells as revealed by dilated ER cisternae ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inside the mitochondria, the protease Lon is a crucial regulator responsible for mitochondrial metabolism and hemostasis [ 134 , 135 ]. Owing to its chaperone activity, mitochondrial Lon controls mitochondrial protein quality, mitochondrial DNA (mtDNA) repair, and ROS production.…”
Section: Overview Of the Impact Of The Tme On Oral Sccmentioning
confidence: 99%
“…Owing to its chaperone activity, mitochondrial Lon controls mitochondrial protein quality, mitochondrial DNA (mtDNA) repair, and ROS production. Therefore, several studies have attempted to elucidate the critical role of mitochondrial Lon in tumorigenic activity, focusing on proliferation, antiapoptosis, and EMT [ 134 , 135 ]. Recent studies have revealed a novel connection between mitochondrial Lon and an immunosuppressive TME in oral cancer [ 136 , 137 ].…”
Section: Overview Of the Impact Of The Tme On Oral Sccmentioning
confidence: 99%
“…For this purpose, mitochondria are equipped with a unique set of proteases dedicated to specific subcompartments. Members of the Lon AAA + -protease fusion family reside in the matrix and degrade denatured or oxidized proteins [ 21 ]. Working in parallel to Lon, ClpP is another matrix-resident ATP-dependent protease which functions together with a AAA + chaperone protein, ClpX [ 22 ].…”
Section: Introduction—modes Of Mitochondrial Protein Quality Contrmentioning
confidence: 99%